Clinical application of platelet-rich fibrin to enhance dental implant stability: A systematic review and meta-analysis. Issue 2 (February 2023) - Guan, Shuai; Xiao, Tiepeng; Bai, Jiuping; Ning, Chunliu; Zhang, Xingkui; Yang, Lei; Li, Xiangjun
Abstract: Objective: To investigate the effect of platelet-rich fibrin application on implant stability. Study design: Five databases, namely, PubMed, Embase, Web of Science, Wiley, and China National Knowledge Infrastructure, were searched for reports published up to November 20, 2022. Randomized controlled trials (RCT), including parallel RCTs and split-mouth RCTs, with at least 10 patients/sites were considered for inclusion. Results: After screening based on the inclusion criteria, ten RCTs were included. Low heterogeneity was observed in study characteristics, outcome variables, and estimation scales (I 2  = 27.2%, P = 0.19). The qualitative and meta-analysis results showed that PRF increased the effect of implant stabilizers after implant surgery. Conclusions: The results of the present systematic review and meta-analysis suggest that PRF can increase implant stability after implant surgery. PRF may also have a role in accelerating bone healing and tends to promote new bone formation at the implant site.